Teacher Research and Evaluation: A Story From Two Perspectives (LEARNing Landscapes, 2015)
We have been fortunate to work with teachers at a 6-12 charter school who have taken the time to challenge themselves, to take a hard look at what is going on in their classrooms in terms of teaching and learning, reflect on what is working, what could be better, question how effective they are, and then share their reflections, their successes, and their doubts with each other. This project started out as voluntary and was changed to being mandatory and a part of the yearly teacher evaluation. We share our individual perspectives on this situation, and how it is unfolding.
Keywords: teacher research; evaluation; teaching; reflection